2014
DOI: 10.1159/000369241
|View full text |Cite
|
Sign up to set email alerts
|

Making Cytological Diagnoses on Digital Images Using the iPath Network

Abstract: Background: The iPath telemedicine platform Basel is mainly used for histological and cytological consultations, but also serves as a valuable learning tool. Aim: To study the level of accuracy in making diagnoses based on still images achieved by experienced cytopathologists, to identify limiting factors, and to provide a cytological image series as a learning set. Method: Images from 167 consecutive cytological specimens of different origin were uploaded on the iPath platform and evaluated by four cytopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The majority of international telecytology studies reported overall concordance rates above 80%, with a range of 71%‐93% (Table ). This is comparable to the concordances rates published from other studies comparing diagnoses made by digital still images to reference glass slides, which vary from 80% to 95% . Reported concordance and accuracy rates for dynamic telecytology are higher, at 95%‐97% concordance and 99% accuracy, perhaps owing to better selection of diagnostic materials up front by viewing the entire slide in real‐time.…”
Section: International Telecytology Studies: How Do They Compare To Asupporting
confidence: 79%
See 3 more Smart Citations
“…The majority of international telecytology studies reported overall concordance rates above 80%, with a range of 71%‐93% (Table ). This is comparable to the concordances rates published from other studies comparing diagnoses made by digital still images to reference glass slides, which vary from 80% to 95% . Reported concordance and accuracy rates for dynamic telecytology are higher, at 95%‐97% concordance and 99% accuracy, perhaps owing to better selection of diagnostic materials up front by viewing the entire slide in real‐time.…”
Section: International Telecytology Studies: How Do They Compare To Asupporting
confidence: 79%
“…International telepathology consultation services with digital whole slide image capabilities have been established at several academic medical centers, including the University of Pittsburgh Medical Center (UPMC), the University of California at Los Angeles (UCLA), and the University of Utah through Associated Regional and University Pathologists (ARUP) Laboratories (Dr. Rosai Surgical Pathology Consultative Services) . Other platforms for international telepathology consultation include the iPath network, MECEMS (the Medical Electronic Consultation Expert system), and the Virtual International Pathology Institute (VIPI) . Despite the range of international telepathology consultation services available, very few studies on international telecytology in clinical practice using WSI have been published.…”
Section: International Telecytology In Clinical Practice: Whole Slidementioning
confidence: 99%
See 2 more Smart Citations
“…20 The iPath platform provides expert pathologic review for colleagues in developing countries. 21 In addition, the SickKids-Caribbean Initiative 22 is a regional program sponsored by the Hospital for Sick Children in Toronto, Canada, to build capacity in six Caribbean countries to improve the outcomes of children with cancers and blood disorders. Other projects to improve care for specific underserved areas within the U.S. include the Pacific Island Health Care Project, 23 which provides expert care to the indigenous people of the U.S.-associated Pacific Islands, and the Kansas University Center for Telemedicine & Telehealth, 24 which provides clinical and educational support for several underserved areas in Kansas.…”
Section: Discussionmentioning
confidence: 99%